2019
DOI: 10.1007/s00421-018-04065-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiogenic cell response to sprint interval and continuous exercise

Abstract: Although commonly understood as immune cells, certain T lymphocyte and monocyte subsets have angiogenic potential, contributing to blood vessel growth and repair. These cells are highly exercise responsive and may contribute to the cardiovascular benefits seen with exercise. Purpose: To compare the effects of a single bout of continuous (CONTEX) and sprint interval exercise (SPRINT) on circulating angiogenic cells (CAC) in healthy recreationally active adults. Methods: Twelve participants (aged 29 ±2y, BMI 25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 41 publications
2
22
3
Order By: Relevance
“…Comparing our findings of an increase in CAC numbers directly after an acute bout of exercise with existing literature, we find an agreement with previously published reports of CAC (Shill et al, 2016;O'Carroll et al, 2019), EPC (Bonsignore et al, 2010;Krüger et al, 2015;Montgomery et al, 2019), and HPC kinetics (Krüger et al, 2015;Baker et al, 2017). However, it is apparent that their definitions vary and especially for HPCs CD31-expression is usually not taken into account; Krüger et al (2015) found acute exercise to increase HPCs defined as CD34 + /CD45 + , while Baker et al (2017) defined them only as CD34 + and also found numbers to be increased after exercising at a high but not at a moderate intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing our findings of an increase in CAC numbers directly after an acute bout of exercise with existing literature, we find an agreement with previously published reports of CAC (Shill et al, 2016;O'Carroll et al, 2019), EPC (Bonsignore et al, 2010;Krüger et al, 2015;Montgomery et al, 2019), and HPC kinetics (Krüger et al, 2015;Baker et al, 2017). However, it is apparent that their definitions vary and especially for HPCs CD31-expression is usually not taken into account; Krüger et al (2015) found acute exercise to increase HPCs defined as CD34 + /CD45 + , while Baker et al (2017) defined them only as CD34 + and also found numbers to be increased after exercising at a high but not at a moderate intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also in contrast with O'Carroll and colleagues ( O'Carroll et al., 2019 ), who compared a 45-min bout of continuous exercise at 70% peak oxygen uptake with 6 ​× ​20 ​s maximal sprints on a cycle ergometer on circulating lymphocyte counts. LY, CD8 + T, and CD4 + T cell counts were elevated following both trials.…”
Section: Discussioncontrasting
confidence: 99%
“…These increases were significantly higher following interval exercise compared to continuous exercise. This may be due to the higher exercise intensities implemented by O'Carroll et al., ( O'Carroll et al., 2019 ), whereby sprint intervals were ‘maximal effort’ and resulted in mean power outputs of 223 ​± ​6% of the power output at VO 2 peak. In the present study, power outputs corresponded to 130% peak power and 85% V̇O 2 max for SIE and MICE, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis we could not confirm outcomes of single studies reporting differences in the mobilization of stem cells depending on subject-related variables such as age [10,67,73] or training status [40,46,53,60] nor on interventiondependent variables such as intensity [39,41,60,61,64,69], or modality [49]. Only the number of ESCs 12-48 h after exercise was affected with larger effect sizes when percentage of male subjects was greater and when duration or load was higher.…”
Section: Moderator Variablescontrasting
confidence: 73%